The Effect of Energy Consumption, Energy Resources, Economic Growth, and Road Infrastructure on Co2 Emissions in Indonesia - Zulfikar Zulfikar; Sofyan Syahnur; M. Shabri Abd. Majid (Research Collaboration Community (RCC), 2021)
This study aims to analyze the effect of energy resources, energy consumption, and road infrastructure on economic growth and their effect on CO2 emissions in Indonesia. This study uses time series data in Indonesia for the period 2000 to 2019 and the analytical model used is the Auto Regressive Distributed Lag (ARDL) model. The results found in this study are variables that have a significant effect on economic growth in the short term are road infrastructure in the same period, in the previous period, as well as in the previous 2 periods and resources. Meanwhile, the ones that have a significant effect in the long term are road infrastructure and energy resources. Variables that have a significant effect on CO2 emissions in the short term are road infrastructure, energy consumption in the previous period, economic growth in the previous period, energy consumption and energy resources. While the variables that influence in the long term are economic growth and energy resources.